Information System Design of News Cliping Website in the Field of Public Communication at the Information Communication and Passwords (DKIP) Department of Bandung City - Amni, Defrizal (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The Department of Communication and Information and Encryption of the City of Bandung is a regional technical institution engaged in the field of Communication and Informatics facilities and public relations. In carrying out its duties, the Department of Communication and Information and Encryption of Bandung City designed an information system with a news clipping website. This study aims to determine the design of an information system on the news clipping website in the field of public communication at the Information Communications and Encryption Service (DKIP) in the city of Bandung. Framing analysis or framing used in this study is used as a strategy or means to explain the news in DISKOMINFO with Robert N. Entman's model so that a news is organized in conveying goals and is able to become a means of communication that is right on target. This study uses qualitative research methods, while data collection techniques are carried out by reviewing literature, books and other information relevant to the study. The results showed that the application of the website clipping system at the Department of Communication and Information and Encryption in the city of Bandung was not fully organized due to one reason or another such as inadequate human resources and policies that did not fully agree to use news clipping websites as a means of information.